Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Berbantuan Media Video untuk Meningkatkan Hasil Belajar Peserta Didik - NurJanah, Neneng; Afriza, Edi Fitriana; Gumilar, Rendra (LPPM Institut Pendidikan Nusantara Global, 2024)
This research was motivated by the problems that occurred at SMAN 1 Manonjaya, namely the low student learning outcomes. The method used is a quasi-experimental method with the Nonequivalent Control Group Design research design. The results of the research show that there is a difference in the increase in student learning outcomes seen from the average posttest score for the experimental class of 88.00 and the average score for the control class posttest, namely 72.73. These results prove that comparisons in the experimental class can improve student learning outcomes better than the learning process in the control class with material on international economic cooperation in class XI IPS at SMAN 1 Manonjaya.